Effect of Substrate Sodium Content on Crystallization and Photocatalytic Activity of TiO2 Films Prepared by DC Magnetron Sputtering - Henryk Tomaszewski; Karin Eufinger; Hilde Poelman; Dirk Poelman; Roger De Gryse; Philippe F. Smet; Guy B. Marin (International Journal of Photoenergy, 2007)
The effect of sodium content of the glass support on the crystallinity of sputtered TiO2 films and photocatalytic breakdown of ethanol has been studied. It was found that the activity of the as-deposited (amorphous) films does not depend on the type of support used. The chemical composition of the glass support does influence the activity of annealed films. When using soda-lime glass support sodium diffuses into the film upon annealing, suppressing anatase crystallization and decreasing its photocatalytic activity. To decrease the influence of sodium, soda-lime glass coated with an e-beam evaporated SiO2 barrier layer was used with good result. A reduced sodium concentration in the film leads to well crystallized anatase after annealing. An increased photocatalytic activity was observed for these films.